Professional competence of school counselors in guidance and counseling services - Nadhirah, Nadia Aulia; Baiti, Luthvia Zahiro; Budiman, Nandang (ProGCouns: Journal of Professionals in Guidance and Counseling, 2024)
The professional competence of guidance and counseling teachers is an important aspect  and affects the quality of guidance and counseling services provided by school counselor. As a guidance and counseling teacher, it is important and necessary to acquire  professional competencies to facilitate the needs of students at school and to be able to provide the best service in helping students. The school counsellor profession is a job that  is required special requirements so that in the implementation of the services provided  can convince and gain the trust of those who need help. The professional competency standards  of guidance and counseling teachers refer to whether they can  master concepts, live and embody values, provide and demonstrate assistance, and professional  performance of their responsibility. The research method used to  achieve this goal is Systematic Literature Review (SLR). The results of some literature show that  most guidance and counseling teachers have fulfilled professional competencies with high  categories, this is shown by the guidance and counseling services provided in accordance with  existing standards. However, this study also shows that some other guidance and counseling  teachers are still in the medium and low categories. This affects the effectiveness of the services  provided, so that guidance and counseling teachers need to improve their professional  competence.